Area-based yield index insurance brochure: Isabela - Philippine Crop Insurance Corporation.; International Rice Research Institute; PhilRice (2024)
The Philippines is among the most vulnerable countries to natural disasters, primarily due to its geographical location within the Pacific typhoon belt. This exposes the country to an average of 20 typhoons annually, with significant risks from floods and storm surges exacerbated by climate change, which is projected to increase both the frequency and intensity of these events. Given the limited adaptability of small holder farmers, risk transfer mechanisms such as crop insurance are essential for mitigating the impacts of low-probability but high-impact climatic events. The area-based yield (ARBY) index insurance compensates farmers when an area's yield falls below a trigger yield, independent of individual farmer’s harvest. This brochure outlines the advantages of ARBY, detailing the eligibility criteria, claims process for crop loss, and the yield intervals along with their corresponding payouts. Specifically, it provides the yield intervals and associated compensation amounts in Isabela.